الإعلام الفضائي الفسطيني والقانون الدولي الإنساني في خدمة قضايا الأسرى - سحود سميح سليمان عوايص
The problem of the Palestinian prisoners has started since the Israeli occupation of Palestine and evolved legally and humanitarian over the following years. Many experts show that international humanitarian law interacted with the Palestinian media started very late, and was limited to specific issues, and committed to traditional remedies for other issues without trying to spread them from legal perspectives or following their effects in light of changes in the field of international law. The problem of the study is based on an analysis of the content and effectiveness of the Palestinian TVs in serving the issue of prisoners by implementing the international humanitarian law, to raise awareness and publicize their issue. The study also highlights the news coverage of the proposed Palestinian views and their interest. The study aimed to recognize the performance of the Palestinian TVs and its role in serving the issue of prisoners in the Israeli occupation prisons and the extent of using of the provisions of international humanitarian law in its daily media coverage, and the study sought to express a comprehensive view of the Palestinian TV’s media represented by both Al-Aqsa and Palestine channels. To achieve this goal the study adopted a descriptive-analytical approach by employing a content analysis for the major newscasts throughout the year, in both “Al-Aqsa and Palestine” channels beside using the interviews as a secondary tool to enhance the results. The study concluded the performance of the Palestinian TVs did not rise to the level of the prisoner’s issue and their sacrifices. However, the media's using of the international humanitarian law terminology was limited and slight. Moreover, the result shows an absence of adopting a clear editorial policy such as numbers, statistics, and studies to clear their issue, while the current media coverage divided the prisoner’s issue according to partisan or geography classifications.